Pengaruh Kesantunan Masyarakat Indonesia Dalam Bermedia Sosial Terhadap Nation Branding - Eraskha Paskhalia Christalent Diestoni; Chontina Siahaan Siahaan (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2021)
Social media is not only a place for exchanging information, but also a means of communication and interaction that can cross the boundaries of a particular region. However, the existence of social media, which is incompatible with socialization through social media ethics, has created new problems for society. Some of the case studies reviewed by the author are related to Indonesians who are saying a lot of bad words when responding to social media content. This study identifies and understands the impact, the relationship between Indonesian Internet users' attitudes towards social media and the perception of the Indonesian state in the eyes of the world, and the importance of politeness in communication. I am aiming. It uses a qualitative research method, which is a kind of case study approach. The results of the survey explain how bad Indonesian ethics are on social media. Polls have shown that Indonesia is the most rude country on social media, and if you don't deal with it right away, it can damage Indonesia's reputation. Applying ethics to social media is an important part that must be socialized and practiced by all social media users, especially Indonesia. If Indonesia one day becomes an open-minded country, it could be considered the most polite country in the world, both in real life and on social media.